VERIFIKASI METODE UJI ANGKA ENTEROBACTERIACEAE PADA PRODUK SUSU DAN ANALOGNYA SESUAI SNI ISO 21528-2:2017 - Fakhmi Rooslan Hamidi; Dian Indah Octavianingtyas; Inis Nadawati; Evy Ratnasari Ekawati (Jurnal SainHealth, 2023)
Enterobacteriaceae is a group of bacteria that inhabit the digestive tract of humans and animals, capable of causing nosocomial infections and potentially contaminating food products. Dairy products and their analogs are one of the routine food samples tested at the Testing Laboratory of the Balai Besar POM in Surabaya, whose quality and safety must be maintained for consumption by the public. One of the guarantees for the quality of test results is a test method that has been validated and verified. In this study, verification of the Enterobacteriaceae number test method was carried out with reference to SNI ISO 21528-2:2017. The results of the method verification were declared eligible, for the accuracy parameter, which was 102,26%, while for the precision parameter, it was 0,71% I. the sample group that was given the contamination (S+C) and 0,91% in the positive control group (K). It that be concluded that this method can be used in the Testing Laboratory of the Balai Besar POM in Surabaya.Keywords: Method verifications, Enterobacteriaceae, dairy products and their analogs,Â accuracy, precision.